Directive management and/or educational leadership in pandemic time - Kochen, Gladys (Innovaciones Educativas, 2020)
The world’s emergency situation came to question public policies: How are we going back to school? What is the new normalcy?. Therefore, headteachers had to work along with teachers and students who were home and from home. The work implied a follow-up plan, tracking down problems, finding solutions, and above all, redefining the construction of intersectoral policies. This is, evidently, an experience that we cannot afford to forget. Educational planning should be carried out while evaluating, sustaining, and maintaining proximity during and after the pandemic. The return of those who have eventually been left behind shall be considered as well, in order to guarantee the incorporation of technologies into the educational community, with the participation of teachers and families. Planning is necessary. However, it is also necessary to consider whether we do it considering our previous experiences, or we will re-plan for a supposed “normalcy.”